2016
DOI: 10.1021/acs.langmuir.5b04744
|View full text |Cite
|
Sign up to set email alerts
|

Semifluorinated Alkanes at the Air–Water Interface: Tailoring Structure and Rheology at the Molecular Scale

Abstract: Semifluorinated alkanes form monolayers with interesting properties at the air-water interface due to their pronounced amphi-solvophobic nature and the stiffness of the fluorocarbons. In the present work, using a combination of structural and dynamic probes, we investigated how small molecular changes can be used to control the properties of such an interface, in particular its organization, rheology, and reversibility during compression-expansion cycles. Starting from a reference system perfluor(dodecyl)dodec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Also, a similar trend with dispersants was observed in frequency-sweep experiments as shown in Supplementary Material. This response is likely due to phenol molecules disrupting the asphaltene self-association properties, which in turn decreased the elasticity of the asphaltene interface [17,58]. Also, the responses from frequency-sweep experiments showed that the viscoelastic layer (frequency-dependent) was altered to a solid (frequency-independent) film with a higher coverage.…”
Section: B Interfacial Rheology Of Asphaltenes At Air-water Interfacementioning
confidence: 99%
“…Also, a similar trend with dispersants was observed in frequency-sweep experiments as shown in Supplementary Material. This response is likely due to phenol molecules disrupting the asphaltene self-association properties, which in turn decreased the elasticity of the asphaltene interface [17,58]. Also, the responses from frequency-sweep experiments showed that the viscoelastic layer (frequency-dependent) was altered to a solid (frequency-independent) film with a higher coverage.…”
Section: B Interfacial Rheology Of Asphaltenes At Air-water Interfacementioning
confidence: 99%
“…Interfacial rheological measurements are useful because they cleanly decouple contributions of the surface and the bulk and have been extensively used to study liquid–liquid and air–liquid interfaces. Despite its known benefits, interfacial rheology has yet to be used to probe the viscoelastic properties of liquid metal oxide skins. One study used a bicone geometry as an interfacial rheological tool to measure the viscoelastic properties of oxide skin on Galinstan and the effects of HCl addition on the skin .…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of interfacial rheology is applied to understand the viscoelastic properties, which provide the modulus and relaxation behaviour [190] and to gain information about the structure-rheology interplay. The two-dimensional properties for a variety of systems like synthetic (co)polymers [115,191,192], mixed protein layers [193], biomolecules [45,194,195] and low molecular weight molecules [196] have been performed. However, investigations on pure protein layers and their interaction with water-soluble molecules are still challenging.…”
Section: Discussionmentioning
confidence: 99%